ASSA14-03-03 QKI deficiency promotes FoxO1 mediated nitrosative stress and endoplasmic reticulum stress contributing to increased vulnerability to ischaemic injury in diabetic heart. (1st December 2014) - Guo, W; Jiang, T; Lian, C; Wang, H; Zheng, Q; Ma, H
Abstract : Objectives: Hearts of diabetic individuals are susceptible to ischemia/reperfusion (I/R) injury. The RNA-binding protein Quaking (QKI) is known to link intracellular signalling to the cellular survival and QKI dysregulation may contribute to human diseases. However, the function of QKI in diabetic hearts remains unknown. The current study attempted to identify new molecular mechanisms potentially contribute to the susceptibility to ischaemic injury in diabetic myocardium. Methods: Diabetic ob/ob mice or wild-type C57BL/6J mice were subjected to in vivo myocardial I/R. Myocardial infarct size and apoptosis, QKI5 and FoxO1 expression, nitrosative stress (NS) and ER stress were compared. Knockdown of FoxO1 was obtained by intramyocardial injection of FoxO1 specific small interfering RNA (siRNA, 20 μg), and upregulation of QKI5 was acquired by injecting adenovirus encoding-QKI5. Results: Obvious NS stress was observed in myocardium of ob/ob mice represented by elevated iNOS expression, total NO content and nitrotyrosine content. Administration of 1400W or M40401 partly reduced the caspase-3 activity in ob/ob myocardium encountering I/R (p < 0.05). Higher ER stress was also observed represented by increased p-PERK, p-eIF2α and expression of CHOP in ob/ob myocardium. ER stress inhibitor did not affect the excessive NS stress, but partially reduced I/R-induced caspase-3 activity in ob/ob hearts (p < 0.05). FoxO1 was overactivated in ob/ob myocardium, and knockdown of FoxO1 attenuated the both level of NS stress and ER stress (p < 0.05). Furthermore, QKI5 expression was deficient in ob/ob myocardium. Upregulation of QKI5 diminished FoxO1 expression together with NS and ER stress in ob/ob myocardium, further reduced MI/R injury. Finally, QKI5 overexpression destabilised FoxO1 mRNA in cardiomyocytes. Conclusions: These results suggested that QKI5 deficiency contributed to the overactivation of FoxO1 in ob/ob animals and subsequent magnified nitrosative stress and ER stress, which enhances the ischaemic intolerance of diabetic hearts.